Nanomaterials-Based Heating Devices for Cultural Heritage Application: A Patent Survey - Furferi, Rocco; Carfagni, Monica; Volpe, Yary; Governi, Lapo (Micro and Nanosystems, 2016)
Conservation practices are aimed to implement minimal, targeted and less invasive treatments. The conservation profession's challenges and best practices are there- fore becoming more global and mobile, especially when dealing with treatments involving temperature (e.g. painting conservation). The near future of heating devices in art conservation will be with mobile, versatile, accurate and cost effective
Keywords: nanotechnology